Degradable plasma polymer films with tailored hydrolysis behavior. (March 2020) - Kousal, Jaroslav; Krtouš, Zdeněk; Kolářová Rašková, Zuzana; Sedlaříková, Jana; Schäfer, Jan; Kučerová, Liliana; Shelemin, Artem; Solař, Pavel; Hurajová, Anna; Biederman, Hynek; Lehocký, Marián
Abstract: Thin films based on polylactic acid have been prepared using plasma-assisted vacuum thermal deposition under varying RF glow discharge power and characterized in terms of chemical composition and structural homogeneity. As a measure of the degradability of the films their wash-off and hydrolysis behavior were monitored. The properties of the films were found to be tunable to a significant degree by the deposition conditions. Highlights: Thin plasma polymer films based on poly-lactic acid were prepared. Chemical structure of the films well correspond to the original bulk polymer. Higher plasma power used led to lower mass loss after wetting and slower hydrolysis.